To the release of the book "Cultural Foundations of Learning: East and West" by Jin Li - Sergey Filonovich; Jin Li (Voprosy obrazovaniya / Educational Studies Moscow, 2015)
The preface, written by the scientific editor of the translation, Professor S. R. Filonovich, and the author's (Jin Li) introduction to the Russian edition of the book.